Sugar and spite - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Agatha Raisin mystery, 2025)
"Beloved New York Times bestseller M. C. Beaton's cranky, crafty Agatha Raisin-the star of her own hit T.V. series-is back on the case again. When a series of deaths within the small Cotswolds birdwatching community begins to unravel her village, Agatha and her team at Raisin Investigators are certain there has been foul play involved. Now, they must dig up decades' worth of tempestuous relationships and simmering secrets among the birdwatching enthusiasts of the village in order to prevent any further deaths. But with Agatha's own relationship with John Glass on the rocks after he is called away on his job as a cruise ship dance instructor, and Sir Charles Fraith now attempting to step into John's shoes as her lover, Agatha has her work cut out for her. Agatha will have to break out her binoculars and embrace her bitter side to solve the murders and wrangle the sickly-sweet temptations in her own life. Will she be able to gather all the breadcrumbs and put together the clues before she becomes a sitting duck herself?"-- Provided by publisher.